Clays and Clay Minerals, Vol. 58, No. 4, 573–584, 2010. - Tlili, A.; Felhi, M.; Montacer, M. (The Clay Minerals Society, 2010)
The Ypresianphosphatic series of the Gafsa-Metlaoui basin, southwesternTun isia, is represented by an alternation of phosphatic levels and interbedded facies, which are composed of marly clay and silica-rich rocks. The present work aimed to clarify the genesis of palygorskite and sepiolite of the interbedded facies and to understand the depositional environment of the phosphatic series. The interbedded facies of the Stah and Jellabia mines were investigated using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Energy Dispersive X-ray microanalysis (EDX) of individual constituents and their aggregates. The data obtained indicate that samples are made up of francolite, calcite, dolomite, quartz, feldspars, and clay minerals; the latter consist of palygorskite-sepiolite minerals associated with smectite. Observations by SEM revealed the occurrence of palygorskite and sepiolite as fine and filamentous fibers with thread-like facies and coating dolomite, calcite, and a marly matrix. Such features can be considered as textural evidence of authigenic palygorskite-sepiolite. At the bottom of the Stah section, SEM observations revealed that the fine fibers are more abundant within silica-rich rocks. Silica is commonly available due to bacterial activity saturating its environment with the silicic acid required for the formationof palygorskite-sepiolite. Inthe interbedded facies of the Jellabia section, the moderate fibrous clay content and the presence of well crystallized dolomite revealed that the shallowmarine water was characterized by high-Mg and low-Si activities.
Origin And Depositional Environment Of Palygorskite And Sepiolite From The Ypresian Phosphatic Series, Southwestern Tunisia
gsccm58411-tli.pdf -- 1,332KB
Keywords: Periodicals; Geology; Alkalinity; Authigenesis; Bacterial Activity; Sepiolite; Palygorskite